Monotherapy with intravenous vinflunine in patients with advanced or metastatic urothelial cancer after failure of a platinum-containing regimen: a retrospective analysis of german routine data - Hegele, Axel; Goebell, Peter; Matz, Ullrich; Neuhaus, Thomas (Urologia Internationalis, 2014)
Objective: The objective of this retrospective study was to investigate the efficacy and safety of vinflunine monotherapy and the utility of second-line prognostic factors in patients with advanced or metastatic urothelial cancer relapsing/progressing during or after a prior platinum-containing regimen under daily routine clinical conditions in Germany. Methods: The selection was based on the marketing authorization indication and recommendations as well as on the evaluation of second-line prognostic factors issued from prior pivotal trials. Results: Eight centers across Germany provided a total of 21 patient records. Demographic and clinical characteristics were similar to the data previously reported in pivotal trials. Complete and partial response to vinflunine treatment was observed in 1 (4.8%) and 3 (14.3%) patients, respectively, resulting in an overall response rate of 19.1%. The disease control rate reached 47.7%. The median progression-free survival amounted to 4.4 months (95% CI 2.6-6.6), with a median overall survival of 6.2 months (95% CI 3.9-10.7). The observed toxicity profile was manageable and consistent with prior clinical trials: leukopenia (33.3%), neutropenia (9.5%), anemia (9.5%) and hyperglycemia (4.8%). The reported satisfaction rate with the treatment was 90.5 and 61.9% among patients and physicians, respectively. Conclusions: This retrospective study confirms that the clinical outcomes obtained from routine medical practice in Germany with vinflunine in the treatment of advanced/metastatic urothelial cancer are in line with the data observed in prior clinical trials. © 2013 S. Karger AG, Basel.
EVALuna2:16284